Management of high grade primary cerebellar tumours - Zanib Javed; Raheema Sadiq; Muhammad Shahzad Shamim (Journal of the Pakistan Medical Association, 2024)
Cerebellar high-grade gliomas (cHGG) are uncommon in adults, making up only about 1% of all high-grade gliomas. These tumours differ from supratentorial high-grade gliomas (sHGG) in terms of epidemiology, molecular traits, and the age of the patients. cHGG patients are typically younger and show a higher frequency of neurofibromatosis 1 (NF1) mutations, atypical RAS mutations, and H3K27M mutations. Standard treatment includes surgical resection followed by chemotherapy and radiation. Recent studies emphasize the genetic differences between cerebellar and supratentorial tumours, with new treatments targetting specific molecular abnormalities. Immunotherapy has shown limited effectiveness due to the unique tumour environment in cHGG, and further research is required to improve treatment strategies for these rare tumours. Keywords: Cerebellar glioma, high-grade glioma, molecular therapies, immunotherapy.